The Effect of Gap Junctional Coupling on the Spatiotemporal Patterns of Ca2+ Signals and the Harmonization of Ca2+-Related Cellular Responses - Dougoud, Michaël; Vinckenbosch, Laura; Mazza, Christian; Schwaller, Beat; Pecze, László (PLOS Computational Biology, 2016)
Author Summary The calcium ion (Ca2+), a universal signaling molecule, is widely recognized to play a fundamental role in the regulation of various biological processes. Agonist–evoked Ca2+ signals often manifest as rhythmic changes in the cytosolic free Ca2+ concentration (ccyt) called Ca2+ oscillations. Stimuli intensity was found to be proportional to the oscillation frequency and the evoked down-steam cellular response. Stochastic receptor expression in individual cells in a cell population inevitably leads to individually different oscillation frequencies and individually different Ca2+-related cellular responses. However, in many organs, the neighboring cells have to overcome their individually different sensitivity and produce a synchronized response. Gap junctions are integral membrane structures that enable the direct cytoplasmic exchange of Ca2+ ions and InsP3 molecules between neighboring cells. By simulations, we were able to demonstrate how the strength of intercellular gap junctional coupling in relation to stimulus intensity can modify the spatiotemporal patterns of Ca2+ signals and harmonize the Ca2+-related cellular responses via synchronization of oscillation frequency. We demonstrate that the most sensitive cells are the wave initiator cells and that a highly sensitive region plays an important role in the determination of the Ca2+ phase wave direction. This sensitive region will then also progressively determine the global behavior of the entire system.